An emerging economy perspective on corporate sustainability reporting – main actors' views on the current state of affairs in Pakistan - Zeeshan Mahmood; Rehana Kouser; Md. Abdul Kaium Masud (Asian Journal of Sustainability and Social Responsibility (AJSSR), 2019)
The purpose of this paper is to explore the main actors' views on the current state of sustainability reporting in a developing country context. This qualitative study is based on the interviews of 20 individuals and organizations from Pakistan who were identified as main actors involved in the practice of sustainability reporting. This paper draws on the arguments of multiple theoretical frameworks, including legitimacy theory, stakeholders' theory, institutional theory, political cost theory, and signalling theory. Following a semi-structured interview protocol, main actors were asked to share their views on the drivers and barriers of sustainability reporting, sufficiency and suitability of sustainability-related regulation and standards, perceived benefits of sustainability reporting, level of stakeholder engagement and transparency. Interviews were then analysed to compare the viewpoints of different stakeholder groups on various issues. This paper concludes that, like other emerging and developing economies, the practice of sustainability reporting is largely driven by the external forces. Foreign buyers, international professional associations and standard-setting organizations are playing a pivotal role in the emergence and development of sustainability reporting. Sustainability reporting awards also played an important role as they provide the normative basis and intangible benefits for reporting. Despite these external forces driving the emergence and development of SR in Pakistan, the structural and cultural conditions that exist in the societal context of Pakistan significantly impact the disclosure practices and organizational rationales for SR. In particular, weak government structures, lack of awareness and interest in sustainability matters, lack of regulation, lack of enforcement capabilities, lack of a political will has been identified as the main barriers of SR. The paper explores the perceptions of both managerial and non-managerial stakeholders regarding the current state of sustainability reporting in Pakistan.
Keywords: 650; Drivers and barriers; Sustainability reporting; GRI; CSR; Managerial and non-managerial perceptions; Emerging and developing economies; Pakistan